Economic Fluctuations in Sub-Saharan Africa - Melina, Giovanni; Portillo, Rafael (Washington, D.C. : International Monetary Fund, 2018)
We compare business cycle fluctuations in Sub-Saharan African (SSA) countries vis-a-vis the rest of the world. Our main results are as follows: (i) African economies stand out by their macroeconomic volatility, which is is reflected in the volatility of output and other macro variables; (ii) inflation and output tend to be negatively correlated; (iii) unlike advanced economies and emerging markets (EMs), trade balances and current accounts are acyclical in SSA; (iv) the volatility of consumption and investment relative to GDP is larger than in other countries; (v) the cyclicality of consumption and investment is smaller than in advanced economies and EMs; (vi) there is little comovement between consumption and investment; (vii) consumption and investment are strongly positively correlated with imports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet